Pengembangan Pendidikan Agama Islam Untuk Membentuk Kecerdasan Emosional Siswa - Slamet Safariani, Ade; Nur Atika, Faizah (Jurnal Pendidikan Agama Islam, 2025)
The education pattern in the modern generation has largely changed, where the current generation of students is less concerned with their emotional side. Education only focuses on academics. In fact, emotional intelligence is an aspect that is no less important to pay attention to. The relationship between Islamic Religious Education and emotional intelligence is very close. Through Islamic education, every human being is expected to be able to apply Islamic guidelines in their daily lives and be able to control themselves in their attitudes, so that the results can affect the personal development of students, both in social and academic environments. The method used is a type of field research in this study using a qualitative descriptive research approach. The results of this study indicate that Islamic Religious Education plays an important role in shaping students' emotional intelligence through various learning activities and religious activities. Starting from planning, implementation, and strategies and evaluations that can shape emotional intelligence so that students' emotional intelligence can be developed through three main aspects, namely self-awareness, understanding of others (social awareness), and the ability to manage relationships (relationship management).